Improving The Egg Quality Trough Addition Of Green Tea In Diet On Laying Hen (Jurnal Ilmu dan Teknologi Hasil Ternak, 2010)
The Research  was conducted to study the effect of green tea  addition in diet to egg weight, egg number, egg yolk colour , fat level and cholesterol level of egg yolk on laying hens. The materials used were 72 laying hens of 28 weeks old. The method of  the research was experiment arranged in Completely Randomized Design. The treatment were green tea  addition levels were 0 %, 1 %, 2 %, and 3 %. The variables observed were  egg weight,  egg number,  egg yolk colour, fat level and cholesterol level of  egg yolk. The result showed that green tea  had no significant effect  (P> 0.05) on egg weight, egg number and  egg yolk colour, but significant effect  (P<0.05) on fat level and cholesterol level of egg yolk. The conclusion was  green tea  addition  3 % in diets,  had not decreased on egg weight, egg number and not effect on egg yolk colour,  but had decreased fat level and cholesterol level of egg yolk on laying hens. The suggested were on management of laying hen, so addition  2 %  green tea on diets for reducing   fat level and cholesterol level  of egg yolk,  with optimal egg production.   Keywords : Laying hen, Green tea, Egg yolk colour, Fat, Cholesterol